Comparison of LAMP and PCR for the Diagnosis of Methicillin-Resistance Staphylococcus Aureus (MRSA) Isolated from Different Food Sources - Jassim, Sundus Ali; Kandala, Nuha; Fakhry, Saad Sabah (Iraqi Journal of Science, 2021)
Staphylococcus aureus, which includes the methicillin-resistant S. aureus (MRSA), is a significant human pathogen producing different toxins and results in many different infection types, which include bacteremia, soft-tissue infections, as well as staphylococcal food poisoning. S. aureus is an important food-borne pathogen of humans due to ingestion of food containing enterotoxigenic strains. Detecting S. aureus femA and mecA genes was evaluated with the use of a Loop-mediated Isothermal Amplification Method (LAMP). The accuracy of this approach was similar to that attained using the approach of the conventional polymerase chain (PCR). Those two methods characterized 43 isolates of MRSA which were separated from different samples of foods and were not detected in the two other non-Staphylococcus strains (standard strains). The optimal temperature for the LAMP assay was 65°C, with a detection limit of 2.5ng/μL and 103cfu/ml, when compared to 12.5 ng/μL and 104cfu/ml for PCR. The LAMP assay permits a one-step characterization of a specific gene, with no special equipment, and needs less time compared to the traditional PCR. It is assumed that the LAMP assay is a promising alternative method for the rapid identification of S. aureus and could be used in resource-limited laboratories and fields.